Development of Early Childhood Character Learning Model Based on Local Wisdom of Kalimantan Folklore (BEKANTAN) - Ahmad Suriansyah; Aslamiah; Rizky Amelia (SEAMEO CECCEP, 2021)
This study aims to explore the values of character education in Kalimantan folklore and their role in shaping the character of early childhood. The approach used is the concept of children's literature and character education. Kalimantan folklore is still rarely heard, especially in kindergarten, even though it has been a bedtime story for children since ancient times. Through this research, a character learning mode develops using Kalimantan folklore as a material to transfer values, norms, and culture in the development of AUD character. This study uses a Research and Development (R & D) approach. The setting of this development research was carried out at PAUD Lab school ULM; considering the conditions of the covid-19 pandemic, the implementation of this research trial used a teacher visit and home visit strategy. The steps of this research are: 1) data collection, 2) planning, 3) model preparation, 4) expert validity test, 5) product revision, 6) field trial, 7) product revision, and 8) dissemination and implementation. The resulting model is a conceptual model of character learning based on local wisdom of Kalimantan folklore which shorts to BEKANTAN. The BEKANTAN model is an acronym for Early Childhood Character Learning Based on Local Wisdom in Kalimantan Folklore. Researchers chose the philosophy of the acronym BEKANTAN because this animal is a characteristic of South Kalimantan, which only exists in Kalimantan and is part of Kalimantan's local wisdom. The study results explain that the value of local knowledge that package through the story of Semangka Emas and Putri Junjung Buih can apply several character values for children. Character values include helping each other, not being stingy, helping sincerely, not being greedy, independent in conveying ideas, working together in groups, discipline, honesty, democracy, and responsibility in carrying out tasks.